The Predictors of Preventive Behaviors of Crimean-Congo Hemorrhagic Fever in Zabol Ranchers Based on Health Belief Model - Gholamreza Masoudy; Mehdi Karimi-aval; Alireza Ansari; Mohammad Hadi Abasi; Mohammad Abaszadeh-bazi (Iranian Association of Health Education and Health Promotion, 2016)
Background and objective: Crimean-Congo Hemorrhagic fever (CCHF) is a viral zoonosis transmitted by ticks. Determining the predictors of preventive behaviors of this disease and designing a structured educational intervention has an important role in promoting the health of all people who are directly or indirectly exposed to this dangerous disease, including ranchers and their families. The aim of this study was to determine the preventive behavior predictors in ranchers in Zabol. Materials and methods: In this cross-sectional study, 200 rural ranchers by a multi-stage sampling method randomly were selected and surveyed. The data were collected via a multi-section questionnaire that was developed based on the health belief model and its validity and reliability was confirmed by experts and Cornbrash's alpha coefficient (α= 0.72). The data were analyzed in SPSS 16 using descriptive and analytic statistics (percentage, mean, Pearson Correlation coefficient and linear regression test).The significant level was set at 0.05. Results: 91.5%, 46.5% and 31.5% of participants, respectively, were male, illiterate and rancher and over about 50% of them had butchered an animal in the past. Results also showed that preventive behaviors of CCHF have a positive significant association with perceived benefit and perceived self-efficacy, and also results of linear regression test showed that self-efficacy forecasted 11% of behavior variances in participants. Conclusion: Maintaining and improving the ranchers health against the risk of CCHF in tropical regions, particularly in the Sistan region in Sistan and Bloochestan province is an educational urgency and interventions based on the health belief model should emphasize more on the self-efficacy and perceived susceptibility. Paper Type: Research Article.